Penggunaan Film Kartun Dalam Pembelajaran Bahasa Arab Tingkat SMP: Systematic Literature Review - Az Zaky, Yazid Abid; Fahmi, Ari Khairurrijal (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
In the current digital era, educational methodologies are evolving at an unprecedented pace, making it crucial to explore innovative teaching tools. Cartoons, with their engaging and interactive nature, present a compelling medium for Arabic language learning, particularly for young children. This research aims to describe the need for Arabic language education development by exploring learning media using cartoons. The method utilized in this study is systematic literature review, employing meta-synthesis procedures. The research findings indicate that the use of cartoons in Arabic language learning in the digital era positively impacts student engagement and understanding of learning materials. Overall, this study underscores the significance of integrating cartoons into Arabic language education to cater to the needs of elementary school children in today's digital age.